1993
DOI: 10.1002/jez.1402670309
|View full text |Cite
|
Sign up to set email alerts
|

A series of normal stages for development of Scyliorhinus canicula, the lesser spotted dogfish (Chondrichthyes: Scyliorhinidae)

Abstract: By observing numerous living eggs from the lesser spotted dogfish Scyliorhinus canicula (L.) caught near Roscoff (France) and reared at recorded temperatures as they developed from first cleavage to hatching, the first reasonably complete developmental table was worked out for this classical material in vertebrate embryology. The successive stages, described and numbered from 1 to 34, correct and replace the incomplete stages A-Q proposed by Balfour (J. Anat. Physiol., 10:555-576,1876) and other even less comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
426
1
8

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(465 citation statements)
references
References 12 publications
13
426
1
8
Order By: Relevance
“…Embryonic stagings of S. torazame and L. japonicum were based on Ballard et al (28) and Tahara (29), respectively. Total RNA of S. torazame was extracted from a whole embryo at stage 12.…”
Section: Methodsmentioning
confidence: 99%
“…Embryonic stagings of S. torazame and L. japonicum were based on Ballard et al (28) and Tahara (29), respectively. Total RNA of S. torazame was extracted from a whole embryo at stage 12.…”
Section: Methodsmentioning
confidence: 99%
“…Staged embryos (Ballard et al 1993) were removed from egg cases, anaesthetized (MS222) and tails anterior to the caudal fin were removed. These were processed in 4% PFA for in situ hybridization with a probe for Scshh (S. canicula sonic hedgehog gene), SEM or histological examination.…”
Section: Methodsmentioning
confidence: 99%
“…The results are depicted in Figures 2-7, and embryo staging is as previously described (Ballard et al, 1993). S. canicula gene expression relative to other gnathostomes is summarized in Table 1. S. canicula foxc1 expression in paraxial mesoderm derivatives.…”
Section: Expression Of S Canicula Clustered Fox Genesmentioning
confidence: 99%
“…S. canicula foxq1 marks the pharyngeal endoderm and gill buds. The later start to form at stage 24, presumably to increase the respiratory surface until the onset of pharyngeal respiration at stage 32 when they start to regress (Ballard et al, 1993). However, the function of the gill buds may not be restricted to respiration, and it has been shown that the gill buds of S. canicula are related to the parathyroid of tetrapods and are involved in regulating extracellular calcium levels (Okabe and Graham, 2004).…”
Section: Comparison To Invertebrate Chordates and Clustered Fox Gene mentioning
confidence: 99%